2016
DOI: 10.1002/jhbp.371
|View full text |Cite
|
Sign up to set email alerts
|

Size mismatch in liver transplantation

Abstract: Size mismatch is an unique and inevitable but critical issue in live donor liver transplantation. Unmatched metabolic demand of recipient as well as physiologic mismatch aggravates the damage to liver graft, inevitably leading to graft failure on recipient. Also, an excessive resection of liver graft for better recipient outcome in live donor liver transplant may jeopardize the healthy donor well-being and even put donor life in danger. There is a fine balance between resected graft volume required to meet the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 87 publications
1
51
0
2
Order By: Relevance
“…In addition, the need for high levels of antigen in largefor-size grafts is associated with a high incidence of rejection. 4,6 Consistent with these findings, in our study, intraoperative hypotension was observed more frequently in patients with a G/R > 4%. Because the large graft receives relatively low portal blood flow due to the small recipient size, impairment in hepatic microcirculation may occur.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the need for high levels of antigen in largefor-size grafts is associated with a high incidence of rejection. 4,6 Consistent with these findings, in our study, intraoperative hypotension was observed more frequently in patients with a G/R > 4%. Because the large graft receives relatively low portal blood flow due to the small recipient size, impairment in hepatic microcirculation may occur.…”
Section: Discussionsupporting
confidence: 91%
“…This finding may be explained by an increase in intra-abdominal and intrathoracic pressures, atelectasis, and respiratory failure. 4 In addition, the large-for-size group in our study received more blood product transfusions. This finding may be explained by hypotension due to external compression of the venous system and distribution of volume into the graft.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations